Density Figure of Aedes Aegypti Larvae and Community Participation in Prevention of Dengue Hemorrhagic Fever (DHF) - Carmelia Yunitra Angrida Putri Leri; Agus Setyobudi; Enjelita Mariance Ndoen (Universitas Nusa Cendana, 2021)
The density of Aedes aegypti mosquito larvae is a risk factor for Dengue Hemorrhagic Fever transmission. Density Figure (DF) is a measurement to determine the success of Aedes aegypti control with four leading indicators (House Index/HI, Container Index/CI, Breteau Index/BI, and Larva Free Figure/ABJ). In addition, community participation, manifested in the Mosquito Nest Eradication Movement, is also essential to prevent and control DHF. This study determined the density figure of mosquito larvae and community participation in the DHF prevention in Oesapa Urban Village, Kupang City, in 2021. This research was a descriptive research type with a total sample of 99 households. Data univariably analysis on water container material, water container type, water container cover presence, and community participation. The results showed that most of the respondents used plastic water container material (57.51%), TPA container type (55.09%), and presented uncovered water container (63.05%). The DF of Aedes aegypti mosquito larvae was in the high category with HI (35.36%), CI (51.86%), BI (324.42%), and ABJ of 64.65%. Therefore, the community should be more aware and consistent to apply PSN-DHF, focusing on 3M Plus implementation to reduce the incidence of DHF.